2005
DOI: 10.1161/01.cir.0000162461.67140.4c
|View full text |Cite
|
Sign up to set email alerts
|

Defective Cardiac Ryanodine Receptor Regulation During Atrial Fibrillation

Abstract: Background-Ca2ϩ leak from the sarcoplasmic reticulum (SR) may play an important role in triggering and/or maintaining atrial arrhythmias, including atrial fibrillation (AF). Protein kinase A (PKA) hyperphosphorylation of the cardiac ryanodine receptor (RyR2) resulting in dissociation of the channel-stabilizing subunit calstabin2 (FK506-binding protein or FKBP12.6) causes SR Ca 2ϩ leak in failing hearts and can trigger fatal ventricular arrhythmias. Little is known about the role of RyR2 dysfunction in AF, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
282
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 318 publications
(304 citation statements)
references
References 61 publications
8
282
1
5
Order By: Relevance
“…S7B). Increased phosphorylation of RyR2 channels at Ser-2808, catalyzed by PKA (11,12), and Ser-2814, catalyzed by CaMKII, has been implicated in the arrhythmogenic release of Ca 2+ through leaky RyR2 channels (13,20); however, in contrast to previous reports, neither basal phosphorylation (SI Appendix, Figs. S6 and S7) nor phosphorylation stimulated by agonists of RyR2 at Ser-2808 ( Fig.…”
Section: Kn-93 Reduces Ne-evoked Increases Of I Cal In Patients Withcontrasting
confidence: 58%
See 1 more Smart Citation
“…S7B). Increased phosphorylation of RyR2 channels at Ser-2808, catalyzed by PKA (11,12), and Ser-2814, catalyzed by CaMKII, has been implicated in the arrhythmogenic release of Ca 2+ through leaky RyR2 channels (13,20); however, in contrast to previous reports, neither basal phosphorylation (SI Appendix, Figs. S6 and S7) nor phosphorylation stimulated by agonists of RyR2 at Ser-2808 ( Fig.…”
Section: Kn-93 Reduces Ne-evoked Increases Of I Cal In Patients Withcontrasting
confidence: 58%
“…Spontaneous impulse generation could be related to increased activity of PKA and/or CaMKII, with subsequent uncoordinated release of Ca 2+ from the sarcoplasmic reticulum. Such a concept is attractive, because Ca 2+ released from the "leaky" sarcoplasmic reticulum would activate the Na + -Ca 2+ exchanger to extrude Ca 2+ and to produce a arrhythmogenic depolarizing current, thereby explaining both the contractile dysfunction and the high recurrence rate (11)(12)(13).…”
Section: Fig 1 Bone Cells Express Avprs Immunofluorescence Microgrmentioning
confidence: 99%
“…The increased frequency of potentially arrhythmogenic Ca 2+ sparks and Ca 2+ waves are most likely caused by defective RyR2 channels 5,8,10 . Consistent with these observations, we previously found defects in RyR2 in atrial biopsies of patients in chronic AF.…”
Section: Abnormal Intracellular Ca 2+ Release Channel Activity In Afmentioning
confidence: 99%
“…RyR2 is also regulated by protein kinase A (PKA) phosphorylation, and increased PKA phosphorylation of RyR2 has been observed in patients with atrial fibrillation [7] . Shan et al [57] demonstrated that mice in which RyR2 was constitutively by PKA (RyR2-S2808D knock-in mice) exhibited an increased open probability, more calcium sparks, and increased SR Ca 2+ leak.…”
Section: Wwwnaturecom/aps Mccauley MD Et Almentioning
confidence: 99%
“…There is now considerable evidence that abnormal RyR2-mediated Ca 2+ release from the SR can lead to both atrial [6,7] and ventricular arrhythmias associated with sudden cardiac death [8][9][10] . Increased SR Ca 2+ release during diastole can lead to activation of the Na + /Ca 2+ -exchanger [11] , which in turn generates a transient inward current that can cause afterdepolarizations and triggered action potentials.…”
Section: Introductionmentioning
confidence: 99%